2022
DOI: 10.1002/ana.26416
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Resilience Modulates the Penetrance of Parkinson Disease Genetic Risk Factors

Abstract: The aim of the current study is to understand why some individuals avoid developing Parkinson disease (PD) despite being at relatively high genetic risk, using the largest datasets of individual-level genetic data available. Methods: We calculated polygenic risk score to identify controls and matched PD cases with the highest burden of genetic risk for PD in the discovery cohort (International Parkinson's Disease Genomics Consortium, 7,204 PD cases and 9,412 controls) and validation cohorts (Comprehensive Unbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…In turn, this will enable the collection of data through consortia to support large‐scale analyses of relationships between biological profiles and treatment response. Analogous efforts have been successful in uncovering genetic underpinnings of disease (MEGASTROKE, 35 IPDGC, 35,36 GP2 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…In turn, this will enable the collection of data through consortia to support large‐scale analyses of relationships between biological profiles and treatment response. Analogous efforts have been successful in uncovering genetic underpinnings of disease (MEGASTROKE, 35 IPDGC, 35,36 GP2 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…The related common variant burden has been shown to affect the phenotype in carriers of such variants 5 , 26 , suggesting that the cumulative effect of common variants can modify the penetrance of rare variants in such phenotypes, even when the primary cause is considered monogenic. While the impact of common variants on overall phenotypic expressivity has been examined for several neuropsychiatric 25 , 27 , 28 and other disease cohorts 29 31 , the modification of rare variant penetrance by other rare genetic variants has not been widely investigated because of the large cohort sizes required. Here, we present an analysis of common and rare variant burden in 419,854 adults from the UK Biobank (UKB) 32 .…”
Section: Mainmentioning
confidence: 99%
“…Outside the PD field, it has been suggested that PRSs for common diseases such as coronary artery disease and type 2 diabetes, utilizing much larger sample sizes and improved algorithms, can identify individuals with risk equivalent to monogenic mutations [ 70 ] (although others have argued that the true effect size is likely to be much more modest [ 71–74 ]). Recently, research on genetic resilience factors that mitigate the effects of risk/pathogenic loci and reduce the susceptibility to PD is also emerging from GWA analyses [ 75 ].…”
Section: Evidence For An Important Genetic Role In Pdmentioning
confidence: 99%